Single-incision laparoscopic splenectomy - Joshi Manish; Kurhade Shrikant; Peethambaram M; Kalghatgi Suhas; Narsimhan Mohan; Ardhanari Ramesh (Journal of Minimal Access Surgery, 2011)
Single-incision laparoscopic surgery (SILS) is a rapidly evolving field as a bridge between traditional laparoscopic surgery and natural orifice transluminal endoscopic surgery. We present a case of SILS splenectomy performed with conventional laparoscopic instruments in a 7-month-old boy with the diagnosis of multiple splenic abscesses. A 3-cm umbilical incision was used for the placement of two (5 mm) trocars and one 10-mm videoscope (30º). Conventional laparoscopic dissector and grasper were the main tools during surgical procedure. Spleen was removed through the umbilical incision. Although procedures like aingle-incision cholecystectomy have been reported, to the best of our knowledge this is the first report of SILS splenectomy using conventional laparoscopic instruments reported from India and is perhaps the first in an infant in the world literature.